Action of YM155 on clear cell renal cell carcinoma does not depend on survivin expression levels - Sim, Mei Yi; Huynh, Hung; Go, Mei Lin; Yuen, John Shyi Peng (PLOS ONE, 2017)
The dioxonapthoimidazolium YM155 is a survivin suppressant which has been investigated as an anticancer agent in clinical trials. Here, we investigated its growth inhibitory properties on a panel of immortalized and patient derived renal cell carcinoma (RCC) cell lines which were either deficient in the tumour suppressor von Hippel-Lindau (VHL) protein or possessed a functional copy. Neither the VHL status nor the survivin expression levels of these cell lines influenced their susceptibility to growth inhibition by YM155. Of the various RCC lines, the papillary subtype was more resistant to YM155, suggesting that the therapeutic efficacy of YM155 may be restricted to clear cell subtypes. YM155 was equally potent in cells (RCC786.0) in which survivin expression had been stably silenced or overexpressed, implicating a limited reliance on survivin in the mode of action of YM155. A follow-up in-vitro high throughput RNA microarray identified possible targets of YM155 apart from survivin. Selected genes (ID1, FOXO1, CYLD) that were differentially expressed in YM155-sensitive RCC cells and relevant to RCC pathology were validated with real-time PCR and western immunoblotting analyses. Thus, there is corroboratory evidence that the growth inhibitory activity of YM155 in RCC cell lines is not exclusively mediated by its suppression of survivin. In view of the growing importance of combination therapy in oncology, we showed that a combination of YM155 and sorafenib at ½ x IC50 concentrations was synergistic on RCC786.0 cells. However, when tested intraperitoneally on a murine xenograft model derived from a nephrectomised patient with clear cell RCC, a combination of suboptimal doses of both drugs failed to arrest tumour progression. The absence of synergy in vivo highlighted the need to further optimize the dosing schedules of YM155 and sorafenib, as well as their routes of administration. It also implied that the expression of other oncogenic proteins which YM155 may target is either low or absent in this clear cell RCC.